Laboratory Verification of Electron‐Scale Reconnection Regions Modulated by a Three‐Dimensional Instability. Issue 7 (30th June 2021) - Greess, S.; Egedal, J.; Stanier, A.; Daughton, W.; Olson, J.; Lê, A.; Myers, R.; Millet‐Ayala, A.; Clark, M.; Wallace, J.; Endrizzi, D.; Forest, C.
Abstract: During magnetic reconnection in collisionless space plasma, the electron fluid decouples from the magnetic field within narrow current layers, and theoretical models for this process can be distinguished in terms of their predicted current layer widths. From theory, the off‐diagonal stress in the electron pressure tensor is related to the thermal noncircular orbit motion of electrons around the magnetic field lines. This stress becomes significant when the width of the reconnecting current layer approaches the small characteristic length scale of the electron motion. To aid in situ spacecraft and numerical investigations of reconnection, the structure of the electron diffusion region is here investigated using the Terrestrial Reconnection Experiment. In agreement with the closely matched kinetic simulations, laboratory observations reveal the presence of electron‐scale current layer widths. Although the layers are modulated by a current‐driven instability, three‐dimensional simulations demonstrate that it is the off‐diagonal stress that is responsible for breaking the frozen‐in condition of the electron fluid. Plain Language Summary: "Space weather" describes the conditions of the plasma surrounding the Earth, which can have a severe impact on the functionality of spacecraft as well as the health of human space travelers. Space weather and the dynamics of space plasmas in general are closely linked to the structure and topology of the magnetic fields permeating our solar system. By a process called magnetic reconnection, magnetic field lines can rapidly and suddenly break and reconfigure their connectivity, allowing for an explosive release of magnetic energy. This phenomenon is at the origin of explosive events such as solar flares and is the driver of magnetic storms in the Earth's magnetosphere powering the Auroras. We present new laboratory observations of this near‐Earth reconnection process recreated in the Terrestrial Reconnection Experiment. The experiment provides detailed measurements of the width of the region where the magnetic field lines break, the electron diffusion region (EDR). Consistent with supercomputer simulations of reconnection, the width of the EDR is measured to be set by the fine spatial scale of the electron orbit motions. As such, the observations provide renewed evidence that the reconnection process is mediated by forces of thermal stress related to the electron motion within the reconnection region. Key Points: The structure of the electron diffusion region is important to reconnection in space plasma The widths of laboratory electron reconnection layers match those of kinetic simulations Kinetic simulations show that the electron pressure tensor breaks the electron frozen flux condition